Museum skepticism a history of the display of art in public galleries - Carrier, David 1944- (Duke University Press, 2006)
1. "Beauty and art, history and fame and power" : on entering the Louvre -- 2. Art and power : time travel in the museum -- 3. Museum skeptics -- 4. Picturing museum skepticism -- 5. Art museum narratives -- 6. Isabella Stewart Gardner's museum -- 7. Ernest Fenollosa's history of Asian art -- 8. Albert Barnes's foundation and the place of modernist art within the art museum -- 9. The display of absolutely contemporary art in the J. Paul Getty museum -- 10. The end of the modern public art museum : a tale of two cities -- Conclusion : What the public art museum might become
Includes bibliographical references (p. [269]-304)and index
Keywords: Art museums / Social aspects; Art museums / Philosophy; Art / Exhibition techniques